2021
DOI: 10.3390/foods10081862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Treating Dietary Green Seaweed with Proteolytic and Fibrolytic Enzymes on Physiological and Meat Quality Parameters of Broiler Chickens

Abstract: The use of seaweeds as nutraceuticals in chicken diets is limited by high fibre levels and low protein digestibility. Therefore, we tested the effect of pre-treating dietary seaweed (Ulva sp.) with a combination of protease and fibrolytic enzymes on physiological and meat quality parameters of Cobb 500 broilers. Five dietary treatments were formulated by including untreated (T1); fibrolytic (12 g/kg) enzyme-treated (T2); fibrolytic (12 g/kg) and protease (5 g/kg) enzyme-treated (T3); fibrolytic (12 g/kg) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…These findings support those of Lokaewmanee et al (2012) and Matshogo et al (2020) , who reported that the use of dietary seaweeds in broiler diets does not affect the birds’ health status. The recorded hematological values were within the normal ranges reported for healthy chickens ( Nhlane et al, 2020 ; Matshogo et al, 2021 ). The enzymes, alanine transaminase (ALT) and aspartate aminotransferase ( AST ), are standard biomarkers for diagnosing hepatocellular injury.…”
Section: Discussionsupporting
confidence: 77%
“…These findings support those of Lokaewmanee et al (2012) and Matshogo et al (2020) , who reported that the use of dietary seaweeds in broiler diets does not affect the birds’ health status. The recorded hematological values were within the normal ranges reported for healthy chickens ( Nhlane et al, 2020 ; Matshogo et al, 2021 ). The enzymes, alanine transaminase (ALT) and aspartate aminotransferase ( AST ), are standard biomarkers for diagnosing hepatocellular injury.…”
Section: Discussionsupporting
confidence: 77%
“…Feed enzymes appear as a solution, since Carbohydrate-Active enZymes (CAZymes) were previously supplemented in broiler chicken diets for their ability to degrade intricate matrices of carbohydrates present in microalgae [ 14 , 15 ], macroalgae such as Laminaria digitata [ 16 , 17 ] and Ulva sp. [ 18 , 19 , 20 ] or grains [ 21 , 22 ]. Recently, an in vitro study showed the ability of a recombinant ulvan lyase from family 25 of polysaccharide lyases (PL25) to partially disrupt the U. lactuca cell wall and, thus, release mono- and oligosaccharides and some monounsaturated fatty acids (MUFA) (e.g., 18:1 c 9) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar data were reported by Abudabos et al [ 23 ] who observed that the dietary inclusion of Ulva lactuca (30 g/kg) in broiler chicken had no effect on feed intake and body weight gain. In addition, Matshogo et al [ 24 ] reported that green seaweed meal inclusion in Cobb 500 broiler diets had no effects on overall growth performances. It is possible that in chickens, the presence of non-starch polysaccharides such as cellulose and hemicellulose in seaweeds affect digestibility with no effects on growth performance [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Matshogo et al [ 24 ] reported that green seaweed meal inclusion in Cobb 500 broiler diets had no effects on overall growth performances. It is possible that in chickens, the presence of non-starch polysaccharides such as cellulose and hemicellulose in seaweeds affect digestibility with no effects on growth performance [ 24 ]. In disagreement with our data, Choi et al [ 25 ] reported that dietary supplementation with 0.5% of brown seaweed by-products resulted in higher average daily gain in broiler.…”
Section: Discussionmentioning
confidence: 99%